Sa??de do homem: conhecimento e ades??o ?? estrat??gia de sa??de da fam??lia - Caires, Ediane Santos (2015)
Introduction: The increased morbidity and mortality of males and decreased life expectancy of man, and the lack of prevention habits underlie current discussions of Men's Health in order to seek reflections that bring men to the assistance health through pragmatic change in men's attitude. Objective: To assess the knowledge and adherence to the Family Health Strategy and prostate cancer in men Bahian farmers. Methodology: We conducted two semistructured interviews, where the first had specific issues classified into eight categories: the participation of men in family health strategy (ESF), knowledge about prostate cancer, demand for health services, education level the socio - economic, age, marital status and quality of life. The second interview was conducted by a validated multidimensional instrument for assessing the quality of life, and the SF 36. Results: The sample 354 men, and 328 (92.7%) farmers, with an average age of 57.94 ?? 11, 74 years (40-87), 282 married (79.9%) and 288 (81.6%) with an income equal to the minimum wage. The school was found up to four years of study to 322 men (91.2%). Of the total interviewed 287 subjects (81.1%) know the unity of the Family Health Strategy, however, the demand on health services is mainly for Disease Control 188 men (53.3%) and prevention for 139 men 39.5%. The questioning of the AC Prostate, 340 men (95.80%) have heard about this subject, and 258 people (72.90%) have knowledge of the examinations related to this disease, 149 individuals (42.10%) already performed the rectal exam and 191 respondents (54.20%) PSA testing, on demand of men to health services only 15 subjects (4.2%) of the total interviewed seek health services. Regarding quality of life, there was a significant difference in the field vitality when compared Group 1 characterized by individuals who are part of the ESF with the Group 2 made up of individuals who are not part of the ESF, we find an average of 62, 50 ?? 18.80 vs. 59.93 ?? 21.09 respectively (p = 0.05). Conclusion: It was found that most men had knowledge of pathology and examinations necessary for independent prevention education level. However, when it was discussed the conduct of these tests it was found that half of the men even though endowed with knowledge, did not perform the tests. The education of men to the attention of Prostate CA showed no direct relationship, in relation to preventive tests, it was found that the number of individuals who have not made the digital rectal exam is higher of that feature up to four years of education. The completion of the examination is not subject to family income as men despite having knowledge about the theme does not perform the usual preventive exams. Regarding the quality of life it became clear that the accession of the man prioritized the actions taken by the health team providing a better quality of life to participating users.